South Atlantic Anomaly Areal Extent as a Possible Indicator of Geomagnetic Jerks in the Satellite Era - Campuzano, S. A.; Pavón-Carrasco, F. J.; De Santis, A.; González-López, A.; Qamili, E. (Frontiers in Earth Science, 2021)
Geomagnetic jerks are sudden changes in the geomagnetic field secular variation related to changes in outer core flow patterns. Finding geophysical phenomena related to geomagnetic jerks, provides a vital contribution to better understand the geomagnetic field behavior. Here, we link the geomagnetic jerks occurrence with one of the most relevant features of the geomagnetic field nowadays, the South Atlantic Anomaly (SAA), which is due to the presence of reversed flux patches (RFPs) at the Core-Mantle Boundary (CMB). Our results show that minima of acceleration of the areal extent of SAA calculated using the CHAOS-7 model (CHAOS-7.2 release) coincide with the occurrence of geomagnetic jerks for the last two decades. In addition, a new pulse in the secular acceleration of the radial component of the geomagnetic field has been observed at the CMB, with a maximum in 2016.2 and a minimum in 2017.5. This fact along with the minimum observed in 2017.8 in the acceleration of the areal extent of SAA, could point to a new geomagnetic jerk. We have also analyzed the acceleration of the areal extent of South American and African RFPs at the CMB related to the presence of the SAA at surface and have registered minima in the same periods when they are observed in the SAA at surface. This reinforces the link found and would indicate that physical processes that produce the RFPs, and in turn the SAA evolution, contribute to the core dynamics at the origin of jerks.